Past tense : facing family secrets and finding myself in therapy - Mardou, 1975-; Mardou, 1975- (Avery, an imprint of Penguin Random House, 2024)
When Sacha Mardou turned forty-years-old, she was leading a life that looked perfect on the outside: happily married to the love of her life, enjoying motherhood and her six-year-old daughter, and her first book had just been published. But for reasons she couldn't explain, the anxiety that had always plagued her only seemed to be getting worse. The product of a stoic, working-class British family, Sacha had a deeply seeded distrust of mental health treatment, but now, living the life she'd built in the US and desperate for relief, she finds herself in a therapist's office for the first time. There she begins the real work of growing up: learning to understand her family of origin and the childhood trauma she thought she'd left hidden in the past but is still entangled in her present life. Past Tense takes us inside Sacha's therapy sessions, which over time become life-changing: She begins to come to terms with her turbulent and complicated upbringing, which centered around her now estranged father, who had a violent relationship with her mother and would later go to prison for sexually abusing her stepsister. With her therapist's guidance, she sees how these wounds and other generational trauma has been passed through her family as far back as her grandmother's experiences during The Blitz of World War Two.